Public Libraries and Adult Education: An Historical Review - Jim Killacky (Journal of Research in Rural Education, 1983)
The growth of adult education has created greater needs for learning opportunities in rural areas. The public library is often considered a community learning center with the ability to effectivelyrespond to these needs. This reviewleads to the conclusion that, in the absenceof outside funding, the potential for adult education as a central function of the public library is limited.